The Mediating Role of Academic Passion in Determining the Relationship Between Academic Self-Regulation and Goal Orientation With Academic Burnout Among English Foreign Language (EFL) Learners - Izadpanah, Siros (Frontiers in Psychology, 2023)
One of the most significant current discussions in educational psychology is academic passion. This research aimed to investigate the mediating role of academic passion in the relationship between goal orientation and academic self-regulation with students' academic burnout. So far, however, there has been little discussion about these variables together. The statistical population of the present study includes all undergraduate English students of the Islamic Azad University of Tabriz, whose number is equal to 598 people and the sample size is determined by the convenience sampling method and Cochran's formula (248 participants). Data collection instruments in this study include 4 questionnaires of the academic passion of Fredericks et al. (2004); the goal orientation questionnaire: Elliott and McGregor (2001); the self-regulatory questionnaire of Bofard et al. (1995), and the burnout questionnaire: Bresso et al. (1997) that the validity and reliability of the instruments were confirmed. Pearson test results showed that the correlation coefficient of academic burnout with goal orientation, self-regulatory, and academic passion is statistically significant at 0.05%. These variables are inconsistent with academic burnout, and with increasing these variables, academic burnout significantly decreases. The correlation coefficient of goal orientation with self-regulatory variables and academic passion is statistically significant at the level of 0.05%. These variables are consistent with goal orientation, self-regulated learning, and academic passion, with increasing these variables, they significantly rise. Goal-oriented and self-regulated goal orientation can predict academic passion. Academic passion has a direct and significant relationship with academic self-regulation and goal orientation. Finally, the obtained fit indices of the general model have the desired fit with the collected data. The implication is that academic passion plays an important role in creating a positive learning environment that will lead to effective learning and teaching. It may influence student learning. Passion inspires and stimulates and teaching with passion promotes learning.